Integration of Shariah Economy in Sustainable Business Development: The Role of CSR in Achieving SDG's Goals - Reza Arviciena Sakti; Yudhi Kurniawan Zahari; Septian Adi Prayuda; Abdul Basit (LPPM Universitas Terbuka, 2024)
This research aims to explore the integration of Islamic economic principles in sustainable business development, highlighting the role of Corporate Social Responsibility (CSR) in supporting the achievement of the Sustainable Development Goals (SDGs). Islamic economics, which is based on the values of justice, social responsibility, and balance, offers a relevant framework for businesses committed to sustainability. This research adopts a qualitative approach with literature study and document analysis methods to identify the contribution of Sharia CSR in strengthening the social, economic, and environmental aspects of the SDGs. The results suggest that the application of sharia principles in CSR can enhance positive impacts on communities and the environment, as well as improve corporate reputation sustainably. This integration not only strengthens the company's position in the market, but also contributes significantly to achieving SDGs targets, such as poverty reduction, education enhancement, and environmental preservation. These findings emphasize the importance of adopting Shariah values in corporate CSR strategies to support sustainable businesses that are more inclusive and equitable.